Chemistry dimensions 1 [ VCE units 1 and 2 : VCE units 1 and 2 : Teacher's Resource - Jeffery (Pearson Education Australia, 2007)
Software requiremnet Adobe 6 or greater (provide on this CD), Quick time 6.5 or greater (provide on this CD), Internet Explorer 5x or greater (provide on this CD), Flash player 6 or greater (free download), Microsoft Offices suite